2015
DOI: 10.1002/gps.4405
|View full text |Cite
|
Sign up to set email alerts
|

The comparative efficacy and safety of cholinesterase inhibitors in patients with mild‐to‐moderate Alzheimer's disease: a Bayesian network meta‐analysis

Abstract: BackgroundComparative evidence for efficacy and safety of second‐generation cholinesterase inhibitors (ChEIs) is still sparse.ObjectivesThe purpose of this research is to compare three ChEIs, donepezil, galantamine and rivastigmine, in patients with mild‐to‐moderate Alzheimer's disease (AD).MethodsWe conducted a systematic review for published articles and included randomised, double‐blind, placebo‐controlled trials and head‐to‐head randomised trials evaluating the efficacy and safety of ChEIs in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 44 publications
3
47
0
3
Order By: Relevance
“…Our result was in line with previous studies [54,55], suggesting that AChEIs had greater efficacy than placebo for cognition change assessment. However, with the association between APOE genotype and AD as a major risk factor, APOE ɛ4 is expected to be a potential predictor of response to treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Our result was in line with previous studies [54,55], suggesting that AChEIs had greater efficacy than placebo for cognition change assessment. However, with the association between APOE genotype and AD as a major risk factor, APOE ɛ4 is expected to be a potential predictor of response to treatment.…”
Section: Discussionsupporting
confidence: 83%
“…ChEIs are widely used to treat the symptoms of AD 52,53 , with four agents (tacrine, donepezil, rivastigmine, and galantamine) approved by the U.S. FDA and the European Medicines Agency (EMA). Each of these ChEIs varies from one another in how they inhibit ChE, and in their pharmacokinetics, safety, and long-term efficacy 54 . Furthermore, selective butyrylcholinesterase inhibition increased brain acetylcholine, augmented learning, and reduced Aβ peptide in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a previous pooled analysis of studies on donepezil conducted between 1990 and 1999 revealed that patients allocated to placebo therapy showed slower cognitive decline in more recent trials compared with older trials, despite having more comorbidities 23. Furthermore, our previous network meta-analysis of ChEI therapy revealed an increasing placebo effect on cognitive function over time across various drugs of this class 24. These results suggest that there may have been possible overestimation of the speed of cognitive decline based on Mendiondo’s model in the present study.…”
Section: Discussionmentioning
confidence: 94%